(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2019)
Despite the process of globalization and overall integration, there is a tendency of increasing the value of local resources in the modern world. In positioning of tourist, objects media play one of the most important roles. Media create a kind of image of the positioned tourist destination. It is very important to understand which media channel serves this purpose most profitably. The review of various media channels leads to the conclusion, that not all media channels have the same impact on tourist product promotion. Competent and comprehensive positioning of tourist destinations is possible only with the participation of all media channels, considering the weight of each channel at each specific stage of tourist product promotion.